2012
DOI: 10.1161/circresaha.111.257568
|View full text |Cite
|
Sign up to set email alerts
|

PAR-2 Inhibition Reverses Experimental Pulmonary Hypertension

Abstract: Rationale: A hallmark of the vascular remodeling process underlying pulmonary hypertension (PH) is the aberrant proliferation and migration of pulmonary arterial smooth muscle cells (PASMC). Accumulating evidence suggests that mast cell mediators play a role in the pathogenesis of PH.Objective: In the present study we investigated the importance of protease-activated receptor (PAR)-2 and its ligand mast cell tryptase in the development of PH. Methods and Results:Our results revealed strong increase in PAR-2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 44 publications
4
36
1
1
Order By: Relevance
“…In addition, previous data indicate that thrombin induced a sustained contraction in normal pulmonary arteries by activating PAR-1 [63]. Recently, data were published that indicate a role for PAR-2 expressed on vascular smooth muscle cells in vascular remodeling in pulmonary hypertension [64].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, previous data indicate that thrombin induced a sustained contraction in normal pulmonary arteries by activating PAR-1 [63]. Recently, data were published that indicate a role for PAR-2 expressed on vascular smooth muscle cells in vascular remodeling in pulmonary hypertension [64].…”
Section: Discussionmentioning
confidence: 98%
“…47 Recent studies demonstrated that rivaroxaban treatment, as well as PAR-2 or IL-6 deficiency, attenuates PH in animal models. [48][49][50] Also, there is at least 1 case report in which PH For personal use only. on May 10, 2018. by guest www.bloodjournal.org From improved in a patient treated with an IL-6 receptor-blocking antibody.…”
Section: Discussionmentioning
confidence: 99%
“…For real-time PCR analyses, samples from n ϭ 8 donors and n ϭ 6 -10 IPAH were investigated. Three of 10 utilized IPAH lungs have been previously reported (28). These patients' characteristics are reported in Table 1.…”
Section: Methodsmentioning
confidence: 99%